Successful Dupilumab Administration in Adolescent with Alopecia Areata and Atopic Dermatitis: Clinical Case - Eduard T. Ambarchyan; Vladislav V. Ivanchikov; Anastasiya D. Kuzminova; Polina A. Pyzhyanova; Liana R. Agliullova (Вопросы современной педиатрии, 2024)
Background. Alopecia areata is an autoimmune disease characterized by hair loss that develops with the involvement of CD8+ T-cells of the immune system and cytokines produced by T-helper 2 cells (Th2). Efficacy of alopecia areata management is limited. The one potentially effective variant for treatment of severe forms of alopecia areata complicated with atopic dermatitis (AD) is genetically engineered biologic drug dupilumab (interleukin 4 receptor antagonist that suppresses Th2 response). Clinical case description. 11 years old boy was admitted to the dermatology department with complaints on aggravation of AD and numerous hair loss foci. Dupilumab, 300 mg, was prescribed once every 4 weeks. Severity of erythematous papular rashes significantly decreased within 9 months, as well as irritation intensity. Complete restoration of hair growth was noted in areas of former alopecia areata foci. Conclusion. Dupilumab can be effective in the management of severe forms of alopecia areata in children with comorbid AD. Clinical studies on the efficacy and safety of such therapy are needed to confirm this hypothesis.